2008
DOI: 10.1016/j.jomh.2008.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Social policy, imperiled communities and HIV/AIDS transmission in prisons: a call for zero tolerance

Abstract: HIV/AIDS and African-American male imprisonment contribute to the destruction of African-American communities. African-American men and HIV/AIDS are disproportionately represented throughout all sectors of the criminal justice industry, including the juvenile justice system. The criminal justice system contributes to unacceptably high African-American male imprisonment rates and HIV prevalence directly via the 'war on drugs' and lax enforcement of institutional policy among other things, and indirectly through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Some participants who had spent time in jail described the designation of "special" areas for gay or transgender individuals, and being given the option of either solitary confinement or conforming to normative gender codes, by cutting their braids and being housed with the male population. While not every interaction participants described with law enforcement was problematic, the existence of a pattern of severe maltreatment is unacceptable at any frequency, given the power entrusted in law enforcement officers to act as an arm of the justice system and the mandate of police to keep all citizens safe (Graham et al 2008).…”
Section: Criminal (In)justice Systemmentioning
confidence: 99%
“…Some participants who had spent time in jail described the designation of "special" areas for gay or transgender individuals, and being given the option of either solitary confinement or conforming to normative gender codes, by cutting their braids and being housed with the male population. While not every interaction participants described with law enforcement was problematic, the existence of a pattern of severe maltreatment is unacceptable at any frequency, given the power entrusted in law enforcement officers to act as an arm of the justice system and the mandate of police to keep all citizens safe (Graham et al 2008).…”
Section: Criminal (In)justice Systemmentioning
confidence: 99%
“…At the same time, there is evidence to suggest a connection between incarceration and health status [40,41]. As noted earlier, it has been suggested that stress can lead to poor health outcomes [22].…”
Section: Incarcerationmentioning
confidence: 83%
“…While there are slightly fewer men than women (49% vs. 51%) in the total population, there are now only 83 African American men for every 100 African American women, a phenomenon referred to as “missing men” ( Williams, 2006 ). In other words, 17% of Black men have been forcibly removed from their communities ( Graham, Braithwaite, & Treadwell, 2008 ). The two major factors cited to account for this large discrepancy are incarceration and premature mortality.…”
Section: Underrepresentation Of African Americans In Health Researchmentioning
confidence: 99%